FCGR2A Promoter Methylation and Risks for Intravenous Immunoglobulin Treatment Responses in Kawasaki Disease - Ho-Chang Kuo; Yu-Wen Hsu; Mei-Shin Wu; Peng Yeong Woon; Henry Sung-Ching Wong; Li-Jen Tsai; Ruo-Kai Lin; Sukhontip Klahan; Kai-Sheng Hsieh; Wei-Chiao Chang (Mediators of Inflammation)
Kawasaki disease (KD) is characterized by pediatric systemic vasculitis of an unknown cause. The low affinity immunoglobulin gamma Fc region receptor II-a (FCGR2A) gene was reported to be involved in the susceptibility of KD. DNA methylation is one of the epigenetic mechanisms that control gene expression; thus, we hypothesized that methylation status of CpG islands in FCGR2A promoter associates with the susceptibility and therapeutic outcomes of Kawasaki disease. In this study, 36 KD patients and 24 healthy subjects from out-patient clinic were recruited. Eleven potential methylation sites within the targeted promoter region of FCGR2A were selected for investigation. We marked the eleven methylation sites from A to K. Our results indicated that methylation at the CpG sites G, H, and J associated with the risk of KD. CpG sites B, C, E, F, H, J, and K were found to associate with the outcomes of IVIG treatment. In addition, CpG sites G, J, and K were predicted as transcription factors binding sites for NF-kB, Myc-Max, and SP2, respectively. Our study reported a significant association among the promoter methylation of FCGR2A, susceptibility of KD, and the therapeutic outcomes of IVIG treatment. The methylation levels of CpG sites of FCGR2A gene promoter should be an important marker for optimizing IVIG therapy.